The Marketing Machinery of the United States - Cassels, J. M. (Quarterly Journal of Economics, 1936)
I. General Marketing Channels, 659. — Graphic Summary, 663. — II. Wholesale Marketing, 664. — Relative Importance of Different Types, 665. — Expenses, Credit, Wages, 668. — Organization, 570. — Size, 670. — Chains, 671. — Geographic Distribution, 671. — III. Retail Marketing, 672. — Expenses, Stocks on Hand, Credit, 672. — Organization, 674. — Size, 675. — Chains, 676. — Geographic Distribution, 677. — Conclusion, 677.